Using of multi-phase thermal model of the lattice Boltzmann method for simulation of two-phase Rayleigh–Bénard convective heat transfer - Murtadha M. Al-Zahiwat; Ihab Omar; Shahram Babadoust; Laith S. Sabri; Arian Yazdkhsti; S. Mohammad Sajadi; Abbas Deriszadeh; Nafiseh Emami (Results in Chemistry)
In this study, the neutral scalar thermal model is presented for single-phase and so, a single-phase Rayleigh–Bénard is investigated. The Shan-Chen model is expressed in the isothermal state, and by combining the two models, the mixed Shan-Chen thermal method is presented. Then, using a mixed model, a two-phase Rayleigh–Bénard with the thermal Shan-Chen method is proposed. Two-phase Rayleigh–Bénard convective heat transfer is simulated at the relatively high Rayleigh numbers (105), different Capillary numbers (10−3 to 10−4), and also, various ε parameters (parameters related to the temperature difference and thermal expansion). In two-phase Rayleigh–Bénard convective heat transfer increasing the Rayleigh number leads to the increment of Rayleigh–Bénard convective heat transfer between the hot and cold wall and the temperature gradient enhances in the vicinity of the upper wall, lower wall, and interface. It is worth mentioning, that in the two-phase Rayleigh–Bénard problem, the variations of the interface are changed only by changing the thermal expansion coefficient and the temperature difference between the two walls. The results show that the mixed model can simulate two-phase thermal flows. The stability of this method is the same as the multi-phase isothermal models, and it can be applied well for different state equations and relatively high Rayleigh numbers.